The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2105/ajph.2004.037887
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the New Health Education in Britain 1950s–1970s

Abstract: Advertising has a dual function for British public health. Control or prohibition of mass advertising detrimental to health is a central objective for public health in Britain. Use of mass advertising has also been a more general public health strategy, such as during the initial government responses to HIV/AIDS in the 1980s. We trace the initial significance of mass advertising in public health in Britain in the postwar decades up to the 1970s, identifying smoking as the key issue that helped to define this n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 12 publications
0
40
0
5
Order By: Relevance
“…Malcolm Dean, The Guardian, 5 May 2004 Since publication of a causal link between smoking and lung cancer in the 1950s, the tobacco control movement has been influential in bringing about radical changes in policy, individual smoking behaviour and culture (Berridge & Loughlin, 2005;Berridge, 2007;Mamudu et al, 2011). Recent examples of change include bans on smoking in public places in the UK and several other countries, and the introduction of plain packaging for tobacco products in Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malcolm Dean, The Guardian, 5 May 2004 Since publication of a causal link between smoking and lung cancer in the 1950s, the tobacco control movement has been influential in bringing about radical changes in policy, individual smoking behaviour and culture (Berridge & Loughlin, 2005;Berridge, 2007;Mamudu et al, 2011). Recent examples of change include bans on smoking in public places in the UK and several other countries, and the introduction of plain packaging for tobacco products in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Research concerning the governance of tobacco, smoking, and multi-national tobacco companies spans issues such as: individual freedoms (Bell et al, 2010); corporate social responsibility of the tobacco industry (Moerman & van der Laan, 2005;Palazzo & Richter, 2005;Wiist, 2006); and tobacco control (Trochim et al, 2003), with the latter also being examined in the context of the history of public health science and policy (Berridge, 1999(Berridge, , 2003(Berridge, , 2007. Within this body of public health research, activism and use of the media and advertising have been identified as significant issues (Berridge, 2007;Berridge & Loughlin, 2005;Pennock, 2008;Street, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mit der ärztlichen Standespolitik ging der Fokus auf individualmedizinische Prävention in den Hausarztpraxen einher [8,6]; zusätzlich behinderte die föderale Struktur des Gesundheitswesens die Einbringung zentraler Gesetze zum Ausbau bevölke-rungsbezogener Präventionsmaßnahmen. Mehrmals angestrengte Reformen scheiterten [7,25]. Folglich etablierte sich ein Verständnis von Prävention, welches individualmedizinische und bevölkerungsbe-zogene Ansätze stark polarisierte und damit konzeptionelle Fortschritte blockierte [8].…”
Section: Bundesrepublik Deutschlandunclassified
“…Evidence concerning the health damaging consequences of tobacco first emerged in 1947 (see Berridge 2006; and, as evidence began to accumulate, calls for policy interventions grew louder (Berridge 2006;. In the UK, Action on Smoking and Health (ASH) was established in 1971 (Berridge and Loughlin 2005) and subsequently played a high-profile part in advocacy efforts to encourage policy interventions to address what came to be known as the 'tobacco epidemic' (Lopez et al 1994). A series of UK policy efforts to reduce tobacco use and/or the harms associated with smoking ensued, including health warnings on packs, restrictions, then bans, on tobacco advertising and, more recently, bans on smoking in indoor public places (Cairney 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It begins by assessing claims that tobacco control represents a (rare) example of evidence-based public health policy, before moving on to consider three further potential frameworks, each of which provides additional insights. It draws largely on following sources (though additional texts are referred to in relation to specific points): (i) historical overviews of the 'tobacco wars', notably a series of UK-focused publications by the public health historian, Virginia Berridge (1999;Berridge and Loughlin 2005); (ii) a 2012 twentieth anniversary edition of the journal Tobacco Control; and (iii) a systematic review of evidence relating to tobacco industry strategies to influence tobacco tax policies , the most effective policy lever for reducing tobacco consumption (IARC, 2011). The concluding discussion briefly summarises the analysis and considers what insights this case study offers those interested in studying or improving the role of evidence in policy more broadly.…”
Section: Introductionmentioning
confidence: 99%